THE REGULATION SYSTEM OF LAND ACQUISITION AND ITS COMPENSATION IN JAPAN - Boro, Victor (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
The purpose of this research is to find out the success of Japanese government in land acquisition process over its citizens through the mechanism, regulations and laws applicable in Japan, to determine the cooperation process among organization and public agencies in land acquisition for public purpose and its compesation. Japan is a unitary state with three levels of government, the national level, 47 prefectures and 1741 municipalities. The result of this research indicated that there are four criteria in assessing the business applied: (1) specified type of business; (2) businessman is someone who has sufficient intentions and qualifications in running its business, such as a business license, budget, staffing, so on; (3) the public purpose generated from the project must outweigh the lost natural interests, such as people, environment, nature, landscapes, so on; and (4) urgency and mature preparation in running public purpose projects is an obligation for the company. However, there are some of primary constraints from landowner as following: (1) environmental sustainability and community life; (2) business liability; (3) dissatisfaction with compensation; (4) succession dispute; and (5) territorial boundary disputes of MLIT (Ministry of Land, Infrastructure, Transport and Tourism).